Monthly Bulletin of Statistics, May 2024 - United Nations Department of Economic; Social Affairs (United Nations, 2024)
Each issue of the Monthly Bulletin of Statistics (MBS) presents current economic and social statistics for more than 200 countries and territories of the world. Written in French and English, it contains over 50 tables of monthly and/or annual and quarterly data on a variety of subjects illustrating important economic trends and developments, including population, prices, employment and earnings, energy, manufacturing, transport, construction, international merchandise trade and finance. The annual subscription rate for the Monthly Bulletin of Statistics in print includes access to the MBS Online.